Harmonizing Paths: Unveiling the Dichotomy Between Islamic Education and General Education in Indonesia - Fakhrurazi, Fakhrurazi; Syarifuddin, Ummah Karimah; Alfarisi, Usman; Shofiyah, Siti (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2024)
The objective of this research is to investigate the outcomes of analyzing the educational systems in Indonesia, specifically focusing on Islamic and general education. The literature study approach incorporates a total of 13 sources from books and 33 sources from scientific journals. These sources are utilized to gather data, which is subsequently evaluated in accordance with up-to-date information. The research methodology employed is qualitative. The research findings indicate that the establishment of dualism in Islamic education in Indonesia is a result of the coexistence of Islamic education and general education, which is impacted by the Indonesian political system. The emergence of dualism in Islamic education in Indonesia can be attributed to the presence of a parallel system for implementing educational concepts, particularly in the realms of religious education and general education. The implementation of general education and Islamic education is consistently conducted in accordance with their respective areas of emphasis, regardless of their location. The results of this study suggest that educational policymakers might assess the integration of dualism in Islamic and general education in order to effectively utilize both systems by connecting their knowledge.